Comment on Fochler and de Rijcke’s "Implicated in the indicator game? An experimental debate" - Marilyn Strathern (Engaging Science, Technology, and Society, 2017)
Professor Marilyn Strathern reflects on the essays comprising the ESTS Thematic Collection, "Implicated in the Indicator Game? An Experimental Debate."